Impacto do tabagismo na peri-implantite e falha de implantes dentais: avaliação da qualidade da evidência de meta-análises de estudos observacionais - Santos, Gustavo Marques Sobral dos (2018)
Introduction: Several systematic reviews and meta-analyses have evaluated the relation between smoking, peri-implantitis, and implant failure. With the increasing number of publications in recent years and its importance in the health decision-making process, it is essential to assess the degree of evidence of these studies. Objectives: To evaluate the quality of evidence of meta-analyses of observational studies that assessed the relationship between smoking, peri-implantitis and dental implant failure. Materials and methods: A search was conducted in the PUBMED, Web of Science, Scopus, Lilacs, Cochrane Library databases and grey literature to identify metaanalyses that assessed smoking and its effects on peri-implantitis and/or implant failure. Studies in English, Spanish and Portuguese published from February 2011 period corresponding to the creation of PROSPERO were searched. Meta-analyses of preclinical studies were not included in the study. The evaluation of the methodological quality, general risk of bias and degree of evidence of the included studies was performed by the AMSTAR 2, ROBIS and GRADE tools, respectively. Results: A total of 7 meta-analyses were included. The AMSTAR 2 evaluation indicated that 4 presented moderate methodological quality and 3 were critically low (kappa = 0.659; substantial agreement). ROBIS showed that 4 presented low risk of bias and 3 presented high risk (kappa = 0.589; moderate agreement). GRADE concluded that 5 meta-analyses showed very low evidence, 1 showed low and the other showed moderate evidence. Conclusion: Although meta-analyses evaluating the relationship between smoking, peri-implantitis and failure implants present unfavourable outcomes for smokers, the quality of evidence is low. Therefore, the information available in these meta-analyses should be interpreted with caution to clinical practice.